Case report: Young-onset large vessel ischemic stroke due to hyperhomocysteinemia associated with the C677T polymorphism on 5,10-methylenetetrahydrofolate reductase and multi-vitamin deficiency - Fukae, Jiro; Eguchi, Hiroto; Wada, Yoichi; Fuse, Atsuhito; Chishima, Rika; Nakatani, Mitsuyoshi; Nakajima, Asuka; Hattori, Nobutaka; Shimo, Yasushi (Frontiers in Neurology, 2023)
Hyperhomocysteinemia is an important risk factor for cerebral infarction. Herein, we report on a 30-year-old man previously diagnosed with epilepsy who presented with right hemiplegia and total aphasia. Magnetic resonance imaging showed a fronto-temporal ischemic lesion due to occlusion of the left middle cerebral artery. Clinical testing and imaging demonstrated that he had hyperhomocysteinemia induced by multiple factors including the C677T polymorphism on 5.10-methylenetetrahydrofolate reductase (MTHFR), and multiple vitamin deficiencies. The C677T polymorphism on MTHFR is closely related to hyperhomocysteinemia and folate deficiency in epileptic patients who are taking multiple anti-convulsants. Given hyperhomocysteinemia can independently cause stroke at a young age, physicians should periodically examine plasma homocysteine and serum folic acid levels in epileptic patients who are on long-term regimens of multiple anti-epileptic drugs.